WordPress essentials - Hussey, Tris.; Safari eBooks ([S.l.] : Que Pub., 2011)
"Over three hours on everything you need to get started using WordPress. This video covers from installing WordPress, to settings, recommended plugins, recommended themes, and how to customize your WordPress site without any code! Taught by a leading WordPress expert, WordPress Essentials provides all the tips, tricks, and inside knowledge to help you get the most out of the world's most popular blogging and website platform."--Resource description page.
Title and publication information from title screen.
Date of publication from resource description page (viewed Nov. 1, 2011).
Keywords: WordPress (Electronic resource); Blogs -- Computer programs; Web sites -- Authoring programs; Electronic books